Critical Solid Fraction Point Analysis: Case Study on Cement Mill Machine Diaphragm - Achyarsyah, Mochamad; Puspitasari, Poppy (Universitas Negeri Malang, 2019)
During the solidification process, metal liquids turn into solid geometry units including the riser and gating system. The disruption in the liquid flow often causes shrinkage in the object. Critical Solid Fraction Point is a critical point where the continuous liquid supply turned solid and unable to pour to some sections. Simulation software can predict the critical solid fraction time of an object and the liquid supply behavior. The simulation helps the designer in the casting design. The application of low steel alloys in the cement industry, e.g., the Diaphragm, needs development to minimize the shrinkage. This research aimed to analyze the critical solid fraction point in the diaphragm steel casting products. The primary objective of this research was to predict the critical solid fraction point during solidification, started from the longest time in the riser/feeder using SOLIDCast 8.1.1 casting software and provided improvement recommendation to minimize the shrinkage.